Knowledge, attitude and practice of type 2 diabetic patients of selected outreach clinic, Dharan, Nepal - Chitrakala Nepal; Pallavi Vyas; Richha Bhattarai; Bishwanath Acharya; Kanchan Thapa; Jenesh Singh Shrestha; Robin Maskey; Sanjib K. Sharma (Al Ameen Medical College, 2017)
Background and Objectives: The burden of type 2 Diabetes Mellitus continues to rise and constitutes a real threat especially in the developing world. A cross sectional study was carried out to determine knowledge, attitude and practices regarding lifestyle modifications on type 2 Diabetes Mellitus. Methods: Face to face interview was carried out using structured questionnaire among 89 of patients. The data was analyzed using SPSS16. Results: The study showed that majority of participants was female 51(57.30%), while male were 38(42.70%). Most participants were in the age group 56-65 years 29(32.58%), majority of participants were housewife 27(36.99%) with more female diabetic patients being obese. Respondents had good knowledge 55(61.80%) of the benefits of exercise, weight loss and healthy diet. Majority of respondents 55(61.80%) had good practices in relation to lifestyle modifications. Nevertheless, majority of them 45 (50.56%) had negative attitude toward lifestyle modifications. There was no significant association between the knowledge of patients and fasting blood glucose level (X2=3.09, p=0.078). Conclusions: Despite good knowledge and practice of participants toward healthy lifestyle habits, the attitude regarding lifestyle modifications among type-2 diabetes mellitus patients attending outreach clinic was low. Nevertheless the positive attitude of participants should be encouraged and the implementation of a lifestyle intervention program will help to improve the positive attitude, knowledge and practices of type-2 diabetes mellitus patients for the better management of Diabetes Mellitus.